2008
DOI: 10.1021/jp801996m
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of Propylene Oxide in Water: Vibrational Circular Dichroism, Optical Rotation, and Computer Simulation Studies

Abstract: The solvation of propylene oxide (PO) in water has been studied using vibrational circular dichroism (VCD) spectroscopy, optical rotation dispersion (ORD) spectroscopy, molecular dynamics simulations, and ab initio calculations. VCD and ORD measurements were carried out for PO as neat liquid, in CCl4, and in water solutions. The classical molecular dynamics simulations were carried out for the PO + water binary mixtures at different concentrations, and the solvation information was derived from the radial dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
108
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 41 publications
9
108
0
5
Order By: Relevance
“…A promising, if computationally expensive, alternative is to combine molecular dynamics (MD) simulation with quantum chemical sampling of the solute and explicit solvent molecules. [40][41][42] In an attempt to keep the computational cost of the MD-based approach at a minimum, Kundrat and Autschbach 43,44 have shown that a simple point charge representation of the solvent molecules (water) may be used to simulate explicit solvent effects in the quantum chemical sampling. As noted by these authors, the MD-based scheme may also be used as an alternative to Boltzmann averaging to account for conformational effects.…”
Section: Introductionmentioning
confidence: 99%
“…A promising, if computationally expensive, alternative is to combine molecular dynamics (MD) simulation with quantum chemical sampling of the solute and explicit solvent molecules. [40][41][42] In an attempt to keep the computational cost of the MD-based approach at a minimum, Kundrat and Autschbach 43,44 have shown that a simple point charge representation of the solvent molecules (water) may be used to simulate explicit solvent effects in the quantum chemical sampling. As noted by these authors, the MD-based scheme may also be used as an alternative to Boltzmann averaging to account for conformational effects.…”
Section: Introductionmentioning
confidence: 99%
“…[13] This unique sensitivity also led to the discovery of chirality-transfer phenomena. Fori nstance,c hiral oxiranes in water were found to induce aVCD signal for the H 2 Obending modes, [14] and more recently,a mmonia was shown to become optically active upon interacting with methyl lactate under matrixisolation conditions. [15] Furthermore,chiral induction in an ion pair has been reported by Bas et al [16] This encouraged us to apply VCD spectroscopy to study chirality-induction phenomena in ion-pair-based asymmetric catalysis with the focus on establishing structure-spectra relationships which can be used to predict catalytic selectivity.…”
mentioning
confidence: 99%
“…Second-order Møller-Plesset perturbation theory (MP2) [38] with the basis set 6-311++G(d,p) [39] was chosen because of its proven performance in predicting geometries of organic molecules [40] and their IR spectra [21]. For comparison with the experimental data, the harmonic frequencies have been uniformly scaled with a factor of 0.94.…”
Section: Ab Initio Calculationsmentioning
confidence: 99%
“…It is both rigid and stable, and has one stereogenic center, namely the center carbon atom bonded with the methyl group. PO has been a valuable prototype molecule for theoretical and rotational spectroscopic studies of chiral recognition effects [16,17] and chiroptical activities [18][19][20][21]. A series of rotational spectroscopic studies of PO in its ground vibrational and excited internal rotational states were published [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%